EFEKTIVITAS MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS X - Lestari Lature; Gusnardi; Fenny Trisnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of the Teams Games Tournament (TGT) learning model in improving the learning outcomes of class X students at MAN 1 Pekanbaru. The background of this study is based on the low learning outcomes of students in economics subjects which indicate that many students have not achieved the Learning Objective Achievement Criteria (KKTP). The research method used is quantitative with a One Group Pre Test - Post Test design. The research sample consisted of 32 class X.11 students selected by purposive sampling. Data were collected through learning outcome tests conducted before and after the implementation of the Teams Games Tournament (TGT) model. Data analysis techniques used the Gain Normality Test (N-Gain) and the Paired Sample T Test. The results showed that there was a significant increase in student learning outcomes after the implementation of the Teams Games Tournament model. This study concludes that the Teams Games Tournament learning model is effective in improving student learning outcomes and can be an alternative interesting and interactive learning strategy to increase student motivation and involvement in the teaching and learning process.